2014
DOI: 10.1038/srep03656
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric-detection time-stretch optical microscopy (ATOM) for ultrafast high-contrast cellular imaging in flow

Abstract: Accelerating imaging speed in optical microscopy is often realized at the expense of image contrast, image resolution, and detection sensitivity – a common predicament for advancing high-speed and high-throughput cellular imaging. We here demonstrate a new imaging approach, called asymmetric-detection time-stretch optical microscopy (ATOM), which can deliver ultrafast label-free high-contrast flow imaging with well delineated cellular morphological resolution and in-line optical image amplification to overcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 92 publications
(57 citation statements)
references
References 35 publications
(72 reference statements)
0
56
0
Order By: Relevance
“…The new HDF introduced here can overcome those limitations. The DLR of the new HDF was measured to be ~100 ps/nm per dB at 1060 nm, which is five times better than that of the existing SMFs at this window [24], as shown in Fig. 3(a).…”
Section: The Swept Source At 932 Nm (Ss@932nm)mentioning
confidence: 67%
See 2 more Smart Citations
“…The new HDF introduced here can overcome those limitations. The DLR of the new HDF was measured to be ~100 ps/nm per dB at 1060 nm, which is five times better than that of the existing SMFs at this window [24], as shown in Fig. 3(a).…”
Section: The Swept Source At 932 Nm (Ss@932nm)mentioning
confidence: 67%
“…5. Consequently, a sampling rate of 5 GS/s is sufficient for current time-stretch imaging system at 932 nm, which is almost ten times slower than the previous demonstrations [24]. The field of view (FOV) was measured to be ~190 μm, while a larger FOV can also be achieved by using a wider optical spectrum.…”
Section: The Swept Source At 932 Nm (Ss@932nm)mentioning
confidence: 79%
See 1 more Smart Citation
“…More significantly, we have demonstrated that this system is compatible with both adherent cell culture and biochemically-specific cell capture assay formats -further enlarging the scope of time-stretch imaging, which has predominately been limited to the suspensioncell format [7,[10][11][12]20]. Furthermore, the single-cell phenotypes extracted from the timestretch images are no longer restricted primarily to biophysical properties, but also the molecular signatures (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…2(b)). Note that the image contrast can be further enhanced by accessing the phase contrast through the use of interferometry [11,12], or phase gradient contrast by an asymmetric-detection technique [20]. Notably, interferometric time-stretch imaging can further quantify the phase information of cells, from which a set of biophysical phenotypes can be extracted, e.g.…”
Section: Time-stretch Imaging Of Cell Culture On Spinning Discmentioning
confidence: 99%